2019
DOI: 10.1097/iae.0000000000002295
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Oral Iron Supplementation and Retinal or Subretinal Hemorrhage in the Comparison of Age-Related Macular Degeneration Treatment Trials

Abstract: Among participants of comparison of age-related macular degeneration treatments trials, the use of oral iron supplements was associated with retinal/subretinal hemorrhage in a dose-response manner. Unindicated iron supplementation may be detrimental in patients with wet age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…16 Our previous analysis of CATT data showed that iron use (medication or supplement) was associated with a dose-dependent risk of retinal and subretinal hemorrhage in patients with neovascular AMD. 27 In this study with a low number of patients taking iron medications (n = 15), we found iron medication at a daily dose of 50 mg or more (n = 10) was associated with approximately a doubling of risk of GA in both study eyes ( P = 0.22, Table 2) in multivariate analysis adjusted by the AREDS simple severity scale. Of note, anemia could confound the association between iron medication and GA because temporal macula atrophy due to anemia has been reported in patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 59%
“…16 Our previous analysis of CATT data showed that iron use (medication or supplement) was associated with a dose-dependent risk of retinal and subretinal hemorrhage in patients with neovascular AMD. 27 In this study with a low number of patients taking iron medications (n = 15), we found iron medication at a daily dose of 50 mg or more (n = 10) was associated with approximately a doubling of risk of GA in both study eyes ( P = 0.22, Table 2) in multivariate analysis adjusted by the AREDS simple severity scale. Of note, anemia could confound the association between iron medication and GA because temporal macula atrophy due to anemia has been reported in patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 59%
“…Cd has been found to be significantly higher in blood samples of smokers compared to non-smokers ( Li et al, 2019 ), and is associated with a higher incidence of nAMD ( Kim et al, 2016 ; Park et al, 2015 ). Furthermore, a secondary analysis of the Comparisons of AMD Treatments Trials showed that the use of iron supplements was associated with nAMD in a dose-response manner ( Song et al, 2018 ). Other metal ions such as chromium (Cr), copper (Cu), magnesium (Mg), manganese (Mn), selenium (Se) and zinc (Zn) are known to be involved in cellular antioxidant defense mechanisms ( Lee et al, 2019 ; Salmonowicz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%